March Battalion - Hassel, Sven (London Coorgi Books, 1973)
Into the screaming inferno of the Russian Front the Tank Battalions of Hitler$1 (Bs Penal Regiments were thrown. That was no surprise: these soldiers were pure cannon fodder to the German High Command$1 (Bmen whose lives were considered expendable. And because they were treated like animals, they also learned to live like animals. They stole and cheated in the manner of beasts, and died brutally and bloodily, fighting not only the enemy, but each other. Bestselling author Sven Hassel, whose World War II themed novels have sold more than 52 million copies, tells the gripping story of the soldiers sacrificed in the Fuhrer$1 (Bs Russian Offensive.s
Keywords: World War (1939-1945) -- Military Campaigns